Sequencing analysis of the hole DNA of a mutant gene of Klebsiela pneumoniae resistant against BRL 41897A (KSL 19 Mutant) - M. Kuswandi (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
Previous article reported that three positive transformants of different K.pneumonie resistant mutants against BRL 41897A (KSL 19, KSL38 and KSL62) carrying TnphoA was sequenced. The results showed that the three different transformants of the mutants had different genes inserted TnphoA. Subsequently, we then cloned the wild typeM10 chromosome fragments into pUC18 and recombinants analysed by gel electrophoresis and Southern blotting using HindIII fragment from KIH 19 as aprobe. The clones were designated M19 carrying the hole gene which had an important role in the antibiotic resistantion. The plasmid DNA of positive clone was isolated, analysed by Southern blotting, and sequenced using primers based on sequencing data from KIH19. Sequencing data of KIH19 confirmed the sequence of M19 and the point of insertion of transposon. The amino acid sequence at the N terminus of disrupted gene ksl19 showed the characteristics of features of signal peptide structure. In order to characterise the M19 clone, further complementation analysis was carried out, by transformation of M19 plasmid into KSL19 mutant cell, designated T19, and then checked by gel electrophoresis and sensitivity test. The complementation studies showed that sensitivity to BRL 41897A was restored on transformation of a large (7 kb) fragment of DNA carrying ksl19 geneKey words: Resistant K.pneumoniae KSL19 mutants -BRL41897A, sequencing.